2022
DOI: 10.1155/2022/6565620
|View full text |Cite|
|
Sign up to set email alerts
|

HPV-16 Expression and Loss of Cell Differentiation in Primary Bladder Tumors

Abstract: Objective. Primary bladder tumors have a high degree of malignancy. To investigate the expression of human papillomavirus type 16 (HPV-16) in primary bladder tumors and the loss of cell differentiation and to explore the significance of HPV-16 detection, it is expected to be a disease. Treatment provides a theoretical basis. Methods. Fifty-seven patients with primary bladder tumors admitted to our hospital from January 2019 to January 2022 were selected as the research subjects, and they were divided into HPV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%